Perceptions of first year medical students on medical sociology as reflected in their narrative report - Yu-Maglonzo, Eva Irene D.
Narrative reports could supplement structured feedback. It could provide a broader range of responses which could not elicit from the traditional structured questionnaire. However, few studies have analyzed narrative feedback in the health professions. This study focused on the use of narrative reports to determine the perceptions of First Year Medical Students on Medical Sociology. Implications and directions for improving the curriculum were also derived. Two hundred fifty (250) reflection papers were included in the study. Content analysis was used. It was patterned from Leininger's phases of analysis for qualitative data. The different phases were as follows: documentation of raw data, identification and categorization of component, pattern and contextual analysis, and finally, synthesis and interpretation. Results of the study were classified according to the guide questions given by the faculty to the students in writing their reflection paper. These included the following: most significant experience, ideas learned, helps in learning and hindrances to the learning process. The most significant experience, considered by the students was the workshop. The workshop supplemented the lecture. Through the students' participation, they were able to relate the concepts to certain situations, voice their opinions, reflect and make decision. As to the ideas acquired, they learned about communication skills, clarification of their values and the determinants of health and disease. The content of these learning outcomes were similar to our syllabus. The teaching strategy included the workshop and small group discussion. As to the faculty, the students commented on their instructional abilities, personality and attitudes. Certain aspects of the learning environment such as noise hindered the learning process. Noise was an environmental factor which obstructed the teaching-learning process because students could not concentrate. These categories were analyzed and correlated in the context of the teaching learning principles. The predominating teaching-learning principles identified were meaningfulness, novelty, attainment of cognitive skills such as communication skills and the influence of environmental factors in the learning process. The course was considered meaningful because there was practical application of the theories. For one, the lecture was integrated into the workshop. The novelty of using workshop as a teaching strategy facilitated student learning. Most of the cognitive skills particularly the communication skills were cited as the students' learning outcome. Lastly, the learning environment hindered their learning as evidenced by the various environmental factors which they have cited. Using the perceptions of the students based on their reflection paper, formative evaluation could be accomplished. It could supplement the quantitative data derived from traditional structured questionnaire. From this, we could derive data for faculty evaluation, learning outcome, and course evaluation. As to faculty evaluation, we could derive data or parameter not usually provided by structured questionnaires. As to course evaluation, almost all areas were mentioned by the students except for the grading system. Thus, additional guide question in the narrative report could be incorporated in the future to address such limitation. The learning outcome was expressed in terms of ideas learned by the students. The faculty of the Medical Sociology course at the University of Santo Tomas, through this narrative report, became aware of the unique comments of the students about them, the factors which helped and hindered their learning, their learning outcome, the student evaluation of the course and specific curricular issues such as time allotment and course organization. Based on the students' comments, the department as well as the administration could adopt measures that would address the deficiencies mentioned and continue the tasks recommended by the students. This would then lead to improving the course and enhancing the learning process.